Critical Thinking of Prospective Teachers In Solving Math Problems In Terms of Learning Styles - Cahyono, Budi; Rohman, Ahmad Aunur; Setyawati, Rina Dwi (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
This study aims to identify how the process of critical thinking of prospective teachers in solving mathematical problems in the Department of Mathematics Education, Faculty of Science and Technology, Walisongo State Islamic University, is viewed from a qualitative learning style. The purposive sampling method was used to determine six prospective teachers as research subjects. Each visual, auditory, and kinesthetic learning style is represented by 2 subjects. The auxiliary instruments in this study consisted of a learning style questionnaire, a critical thinking ability test, and an interview guide. Critical thinking indicators were developed through consideration of the main elements of FRISCO, the level of cognitive thinking according to Bloom and the Steps of Problem Solving According to John Dewey. Data processing through the stages of data collection, data reduction, and data verification with the triangulation method. The results of the study show that auditory and kinesthetic learning styles have lower critical thinking process characteristics than visual learning styles in solving math problems. From the interview process it was revealed that the ability to argue based on valid and logical facts, all types of learning styles is still quite low. However, all three have strong potential to develop critical thinking skills through stimulation from educators.